2019
DOI: 10.3847/1538-4357/ab54c1
|View full text |Cite
|
Sign up to set email alerts
|

Fine-scale Explosive Energy Release at Sites of Prospective Magnetic Flux Cancellation in the Core of the Solar Active Region Observed by Hi-C 2.1, IRIS, and SDO

Abstract: The second Hi-C flight (Hi-C2.1) provided unprecedentedly-high spatial and temporal resolution (∼250km, 4.4s) coronal EUV images of Fe IX/X emission at 172Å, of AR 12712 on 29-May-2018, during 18:56:21-19:01:56 UT. Three morphologically-different types (I: dot-like, II: loop-like, III: surge/jetlike) of fine-scale sudden-brightening events (tiny microflares) are seen within and at the ends of an arch filament system in the core of the AR. Although type Is (not reported before) resemble IRIS-bombs (in size, and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
49
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 92 publications
19
49
0
Order By: Relevance
“…So, our results demonstrate that, in cancelling regions, a wide spectrum of ejections can be produced, with a wide range of different temperatures and sizes associated with Ellerman bombs, UV bursts and IRIS bombs and other hot and cool ejections (Yang et al 2013;Vissers et al 2015;Reid et al 2016;Rutten 2016;Nelson et al 2017;Rouppe van der Voort et al 2017;Young et al 2018;Tian et al 2018;Chen et al 2019;Guglielmino et al 2019;Ortiz et al 2020;Tiwari et al 2019;Huang et al 2019;Madjarska 2019). The predicted spatial offsets and time delays for hot and cool ejections are in accordance with observational findings.…”
Section: Discussionsupporting
confidence: 88%
“…So, our results demonstrate that, in cancelling regions, a wide spectrum of ejections can be produced, with a wide range of different temperatures and sizes associated with Ellerman bombs, UV bursts and IRIS bombs and other hot and cool ejections (Yang et al 2013;Vissers et al 2015;Reid et al 2016;Rutten 2016;Nelson et al 2017;Rouppe van der Voort et al 2017;Young et al 2018;Tian et al 2018;Chen et al 2019;Guglielmino et al 2019;Ortiz et al 2020;Tiwari et al 2019;Huang et al 2019;Madjarska 2019). The predicted spatial offsets and time delays for hot and cool ejections are in accordance with observational findings.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, the magnetic set-up of campfires are also similar to the magnetic environment of small-scale events (e.g. jetlets, explosive events, and coronal bright points) that are also seen to occur due to flux cancelation (e.g., Panesar et al 2018bPanesar et al , 2019Tiwari et al 2019;Madjarska 2019).…”
Section: Magnetic Field Evolution At Campfire's Basementioning
confidence: 85%
“…The average lengths of the campfires are smaller than the average lengths of Hi-C 2.1 jet-like events (Panesar et al 2020a) and EUI microjets (Hou et al 2021). The sizes of dot-like campfires are similar or smaller than the sizes of Hi-C 2.1 dot-like events (Tiwari et al 2019). The majority of campfires (40) have durations of less than 10 minutes.…”
Section: Statistical Physical Propertiesmentioning
confidence: 94%

The Magnetic Origin of Solar Campfires

Panesar,
Tiwari,
Berghmans
et al. 2021
Preprint
Self Cite
“…The interpretation of the small jets is based on cartoons showing magnetic reconnection in mixed local magnetic field polarities. The spectra at the reconnection site show bidirectional flows either in the low chromosphere (Joshi et al, 2021b), in the corona (Ruan et al, 2019), or at the top of an emergent minifilament (Tiwari et al, 2019). Large Doppler flows can be found at the reconnection, for example, around +/-100-200 km/s (Joshi et al, 2021b).…”
Section: Rotating Structurementioning
confidence: 95%
“…Cool jets or surges show also such blue/red Dopplershifts parallel to the structure (Figure 7A) (Tian et al, 2014;Ruan et al, 2019). Blue and red shift pattern is not always interpreted as a possible rotation (Schmieder et al, 1983;Tiwari et al, 2019), However, frequently, it is defined that the characteristics of the twisting jet is relatively common and does not depend on the temperature or the coronal environment. Twisting has been found in penumbra jets (Tiwari et al, 2018), and in active region jets (Lu et al, 2019;Joshi et al, 2021b) using Si IV, C II, and Mg II lines observed by the IRIS.…”
Section: Rotating Structurementioning
confidence: 99%